Workshop on Making Coconut Jam for the Family Welfare Development Group (PKK) in Sungai Itik Village - Panjaitan, Ruqiah Ganda Putri; Lorensa, Sisi Marda; Rahmah, Adnin; Mandasari, Junika; Septiani, Uray Rina; Tumiang, Kresensia Imakulata; Setiyawati, Neni; Yenni, Yenni; Reza, Muhammad; Nurhuda, Nurhuda; Irvandi, Dede (International Journal of Public Devotion, 2025)
Coconuts can easily be found in Sungai Itik Village, but so far the diversification of the use of coconuts is still not diverse, even though through the activities of PKK (Family Welfare Empowerment) efforts can be made to diversify the use of coconuts. Coconut jam is an example of a product made from coconuts. Making coconut jam requires easily available ingredients and simple equipment. it's simple so it can be done by PKK. This workshop activity aims to take advantage of the potential that exists in the village of Sungai Itik and produce a diversification of processed coconut products in the form of coconut jam. Several potentials include MSME activities in amplang, ant sugar production, tilapia ponds, plantations (bananas, coconuts), and agriculture (rice). This activity is motivated by the abundant availability of coconuts, but the diversification of processed products from coconuts is still limited to the processing of copra and coconut sugar. The method of implementing workshop activities is divided into identifying potentials and problems, compiling programs, determining target audiences, implementing workshop activities which are divided, evaluating the implementation of activities evaluate the implementation of activities through visits to PKK group representatives and conducting interviews and observing jam making, and finally monitoring after workshop activities. The results of the workshop on making coconut jam which involved the community provided scientific contributions, especially for the PKK group in Sungai Itik Village about how to make coconut jam, then this jam can be used for households so that it can reduce children's food snack expenditure, and coconut jam can also be sold so that it can be additional household financial income.Workshop Pembuatan Selai Kelapa Kepada Kelompok Pemberdayaan Kesejahteraan Keluarga (PKK) Di Desa Sungai ItikABSTRAKBuah kelapa dapat dengan mudah ditemukan di Desa Sungai Itik, namun sejauh ini diversifikasi pemanfaatan buah kelapa masih belum beragam, padahal melalui kegiatan PKK (Pemberdayaan Kesejahteraan) dapat dilakukan upaya untuk diversifikasi pemanfaatan buah kelapa. Selai kelapa merupakan salah satu contoh produk berbahan baku buah kelapa. Pembuatan selai kelapa membutuhkan bahan yang mudah didapat dan peralatan yang sederhana. sederhana sehingga dapat dilakukan oleh kelompok PKK.  Kegiatan workshop ini bertujuan untuk memanfaatkan potensi yang ada di desa Sungai Itik dan menghasilkan diversifikasi produk olahan kelapa berupa selai kelapa. Beberapa potensi meliputi kegiatan UMKM amplang, produksi gula semut, tambak ikan nila, perkebunan (pisang, kelapa), dan pertanian (padi). Kegiatan ini dilatarbelakangi oleh melimpahnya ketersediaan kelapa namun bentuk diversifikasi olahan produk dari kelapa masih terbatas pada pengolahan kopra dan gula kelapa. Metode pelaksanaan kegiatan workshop terbagi menjadi identifikasi potensi dan masalah, penyusunan program, penetapan khalayak sasaran, pelaksanaan kegiatan workshop yang terbagi menjadi dua kegiatan yakni penyampaian materi dan diskusi serta praktik pembuatan selai kelapa, evaluasi pelaksanaan kegiatan melalui kunjungan ke perwakilan grup PKK dan melakukan wawancara serta observasi pembuatan selai, dan terakhir monitoring pasca kegiatan workshop. Hasil workshop pembuatan selai kelapa yang melibatkan masyarakat memberikan sumbangsih keilmuan khususnya bagi kelompok PKK di Desa Sungai Itik tentang bagaimana membuat selai kelapa, selanjutnya selai ini dapat dimanfaatkan untuk rumah tangga sehingga dapat mengurangi pengeluaran jajanan makanan anak, dan selai kelapa dapat pula dijual sehingga dapat menjadi tambahan pemasukan keuangan rumah tangga.Kata Kunci :Workshop; Selai Kelapa; Pemberdayaan; Kesejahteraan Keluarga (PKK)